Pogotena Sehat: Bakti Sosial Pelayanan Vaksinasi Covid-19 Bagi Masyarakat - Anggra Desak; Yohanis Umbu Kaleka; Etheldreda Rosari Garung; Ferdinandus Bele Sole; Engel Bertha H. Gena (Unram Journal of Community Service, 2021)
The purpose of this activity is social services to provide Covid-19 vaccination services for people in Pogotena village – Loura Subdistrict, Southwest Sumba Regency – NTT. This activity was carried out in collaboration with STKIP Weetebula with the National Covid-19 vaccination assistance committee and also Salim Group (Indofood, Indomaret, ACA Insurance) and the Health Ministry of the Republic of Indonesia. The implementation of this activity by a team of lecturers from STKIP Weetebula consisting of three lecturers from the physics education study program, 1 lecturer from PGSD, and 1 lecturer from the Indonesian education study program involving 6 students. The result of this activity, namely: as many as 156 people in pogotena village can be served for vaccination using astrazaneca vaccine type. Some of the obstacles faced in the field are that many people have to go home because they do not qualify for vaccines, such as high blood pressure, the type of vaccine used only Astrazaneca so that it cannot reach people under the age of 18 years, and also services for the community who will do the second vaccine because the type of vaccine used is different from the type of vaccine available. The conclusion of this social service activity is that the community is very happy with the services of lecturers and students and very hopeful that this activity can be done again for residents who have not qualified for vaccines. With this social service activity, the Covid-19 vaccination process can be accelerated so as to realize healthy communities and villages